Weighted inequalities for commutators of Schrödinger-Riesz transforms - Bongioanni, Bruno (2012)
In this work we obtain weighted and weak estimates for the commutator of the Riesz transforms associated to a Schrödinger operator , where V satisfies some reverse-Hölder inequality. The classes of weights as well as the classes of symbols are larger than and BMO corresponding to the classical Riesz transforms.